ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA LOYALITAS KONSUMEN DALAM MENGGUNAKAN JASA TRANSPORTASI PO SUMBER ALAM (Studi kasus pada penumpang bus Sumber Alam jurusan Yogyakarta-Jakarta) - Atsatalada, Nanda; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2012)
This research was motivated by the declining number of consumers and some complaints received by the PO Sumber Alam in the period January 2011 - March 2012 which indicated the decline of consumer satisfaction in PO Sumber Alam. By looking at existing problems, this study aimed to analyze the influence of the service quality consisting of physical evidence, reliability, responsiveness, assurance, and empathy for their impact on consumer satisfaction and consumer loyalty of PO Sumber Alam. Sample in this study are 100 people passanger on PO Sumber Alam Yogyakarta-Jakarta and the reverse direction. The question is given by using a questionnaire consisting of closed and open questions. Respondents' answers were then analyzed by 2-stage regression using SPSS program for Windows. Based on the analysis conducted, it was concluded that the physical evidence, responsiveness, and empathy has a positive and significant impact on customer satisfaction. While the assurance negative effect on customer satisfaction, and reliability no significant effect on customer satisfaction. Then the customer satisfaction has a positive and significant impact on consumer loyalty. The results of this study is expected to be used as information for PO Sumber Alam and further research.